Collaborative historical research in the age of big data : lessons from an interdisciplinary project - Ahnert, Ruth; Griffin, Emma; Ridge, Mia; Tolfo, Giorgia (Cambridge elements., 2023)
'Living with Machines' is the largest digital humanities project ever funded in the UK. This text describes efforts to bring together a team of twenty-three researchers to leverage more than twenty-years' worth of digitisation projects.